2005
DOI: 10.1103/physrevb.71.035335
|View full text |Cite
|
Sign up to set email alerts
|

Quantized conductance through an asymmetric narrow constriction in a three-dimensional electron gas

Abstract: Quantized conductance through an asymmetric narrow constriction in a three-dimensional electron gas Waalkens, Holger CopyrightOther than for strictly personal use, it is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), unless the work is under an open content license (like Creative Commons).Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In figure 3(b), we can identify the MR jumps at V ≃ 10, 20, 50, 90, and 140 mV. The rapid increase of MR at some drain-source voltage values is a direct consequence of the singularity in (17), which takes place when the differential conductance for B = 0 approaches zero.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In figure 3(b), we can identify the MR jumps at V ≃ 10, 20, 50, 90, and 140 mV. The rapid increase of MR at some drain-source voltage values is a direct consequence of the singularity in (17), which takes place when the differential conductance for B = 0 approaches zero.…”
Section: Resultsmentioning
confidence: 93%
“…The influence of the constriction shape on the conductance quantization was considered within the generalized Landauer-Büttkier formalism by Scherbakov et al [16], who demonstrated that the character of conductance quantization significantly depends on the asymmetry of the cross section and the softness of the confinement potential. A comprehensive analysis of this problem has been presented in [17]. The effect of quantum interference caused by the single point-like impurity or a couple of impurities localized in the constriction has been a subject of papers by Avotina et al [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…From (20) and noting that n ¼ adnðk; qÞ=cnðk; qÞ we see that r ¼ aq0tnðk; qÞ is proportional to x and this is the motivation for the transformation (141). The scaling of the wavefunction (142) is performed in order to again obtain a system of type ''kinetic-plus-potential".…”
Section: Exact Computation Of Resonancesmentioning
confidence: 98%
“…The quantum transmission problem (without resonances) through a constriction of the type (2) has been studied by Yosefin and Kaveh [18]. Similarly, the transmission problem (again without resonances) has been studied for an axially symmetric hyperboloidal constriction in 3D by Torres, Pascual and Sáenz [19], and for the asymmetric case by Waalkens [20]. The main purpose of the present paper is to study the quantum transmission and the assoicated resonances through the 2D and 3D constrictions (2) and (4) in a coherent way using the perspective of transition state theory.…”
Section: The Transmission Problemmentioning
confidence: 99%
“…24 Besides, the quantization of the conductance in the nanosystems has been experimentally confirmed more recently, 25 although this quantum effect in the 3D nanowires has been predicted much earlier. [26][27][28] The quantization of the conductance is difficult to observe in the real nanowires due to the presence of structural and substitutional disorder, and because of the boundary roughness. 25 This stems from the fact that scattering of conduction electrons on impurities or on structural imperfections results in the change of momentum (the momentum relaxation), which leads to smearing of the step-like form of the electric conductance.…”
mentioning
confidence: 99%